Calidad en el servicio y satisfacción del cliente del supermercado Los Portales de la Ciudad de Iquitos – 2020 - Salazar Quiroz, Edwin Apolinario (2023)
The research problem posed for this thesis: What is the relationship between the quality of service and customer satisfaction in the Los Portales supermarket in the city of Iquitos 2020? At the same time, its objective sought to determine the relationship between the quality of service and customer satisfaction in the Los Portales supermarket in the city of Iquitos 2020; In addition, the specific objectives are to determine the relationship between tangibility, security, reliability, empathy, responsiveness, with customer satisfaction in this study. The methodology used is the quantitative type study; In addition, the questionnaire was used as an instrument for data collection, using the survey as a technique. After processing the data, the following result was obtained: Through the normality test using the Kolmogorov-Smirnov statistic (50 cases or more), a significance of 0.000 is observed for both variables, so that, at the lowest expected p-value (0.05) it is determined that there is no normal distribution of the processed data, which leads us to take Spearman's Rho correlation statistic into account. For the main hypothesis: it is confirmed that "there is a relationship between the quality of service and customer satisfaction in the Portales supermarket in the city of Iquitos 2019, the relationship statistic between the study variables is observed, with which it was obtained As a result, a significant positive correlation coefficient of 0.716, and with a (bilateral) significance of 0.000, which is lower than the probability indicator (0.05 = 5%), the main hypothesis is accepted. The conclusion for this investigation is that the alternative hypothesis is accepted.